Venous thromboembolism is associated with increased all-cause mortality in ALK-positive non-small cell lung cancer - Magdalena Zaborowska-Szmit; Sebastian Szmit; Marta Olszyna-Serementa; Katarzyna Zajda; Anna Janowicz-Żebrowska; Piotr Jaśkiewicz; Dariusz M. Kowalski; Maciej Krzakowski (Cardio-Oncology)
Abstract Background Venous thromboembolic events (VTE) are often diagnosed in ALK-positive lung cancer although it has not been demonstrated how their co-occurrence affects patients' survival. Methods The study included patients with ALK-positive lung cancer recognized in metastatic stage in the period 2017–2022. All received treatment with ALK inhibitors at The Maria Sklodowska-Curie National Research Institute of Oncology in Warsaw. The main aim of the study was to assess overall survival (OS) in relation to VTE occurrence. The additional purpose was to define predictors of VTE and OS. Results The study included 54 patients in median age 60 years, men were a minority (25 / 46.3%). VTE was diagnosed in 12 (22.2%) patients: 9 (16.7%) cases with pulmonary embolism (PE), 2 cases with thrombosis in vena cava superior, one case with deep vein thrombosis and thrombosis in vena cava inferior. Among patients with PE: 2 patients died directly due to the first PE episode and one due to a recurrent PE. Patients with VTE had significantly shorter overall survival (median 11.7 vs. 37.4 months, log-rank test p = 0.003). The risk of all-cause mortality was increased significantly in both: VTE (HR = 3.47; 95%CI: 1.61—7.49; p = 0.0016) or alone PE (HR = 2.41; 95%CI: 1.06—5.50; p = 0.037). The risk of VTE diagnosis was significantly increased during active treatment with crizotinib (HR = 8.72; p = 0.0004) or alectinib (HR = 21.47; p = 0.000002). Metastases to liver and baseline leukocyte count > 11 × 10⁹/L were significant predictors of VTE and OS. Khorana score ≥ 3 points predicted OS (HR = 2,66; 95%CI: 1,05—6,75; p = 0,04), but remained insignificant for VTE. Conclusion The diagnosis of any type of VTE or alone PE was associated with significantly worse overall survival in patients with ALK-positive non-small cell lung cancer.